2020
DOI: 10.1186/s13601-020-00313-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nasal irrigation on allergic rhinitis control in children; complementarity between CARAT and MASK outcomes

Abstract: Background: Nasal irrigations (NI) are increasingly used as an over-the-counter adjunctive treatment for allergic rhinitis (AR), but clinical studies on their effectiveness are limited.Methods: An open-label, controlled, non-randomized, real-life study was conducted to evaluate the effectiveness of NI with a new hypertonic solution as add-on treatment for AR. Children and adolescents with AR were prescribed symptomatic treatment. The active group also received an additional sea-water NI solution supplemented w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Multiple reports assessing nasal irrigation have demonstrated its effectiveness in treating seasonal allergic rhinitis in adult and pediatric patients [ 24 26 ]. Seawater nasal irrigation, as utilized in the present trial, represents a simple method with high reproducibility and facile execution.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple reports assessing nasal irrigation have demonstrated its effectiveness in treating seasonal allergic rhinitis in adult and pediatric patients [ 24 26 ]. Seawater nasal irrigation, as utilized in the present trial, represents a simple method with high reproducibility and facile execution.…”
Section: Discussionmentioning
confidence: 99%
“…126 Recently, a real-life study in children showed significant improvement of AR symptoms and reduction in medications, as these were assessed by VAS and CARAT when nasal irrigation was added to standard treatment. 127 Use of nasal filters in AR adults with grass allergy during a natural in-season exposure demonstrated significant efficacy by means of an improved nasal symptom score, while their safety and usability were also documented. 128 It is, however, uncertain whether such intervention may be tolerable in children.…”
Section: Complementary Therapiesmentioning
confidence: 97%
“…MASK is based on:  An App for rhinitis and asthma developed by the MACVIA-France EIP on AHA reference site (Allergy Diary, now MASK-air ® ), available in 27 countries and fully validated (1);  An interoperable electronic clinical decision support system (CDSS) (6);  A n i n t e r o p e r a b l e w e b -b a s e d p h y s i c i a n 's questionnaire (7) and  An EIT Health project POLLAR (Impact of air POLLution on Asthma and Rhinitis) which predicts alerts for pollen and pollution peaks (8). MASK has led to:  A better understanding of rhinitis in terms of phenotypes and management (1,9);  A better understanding of the links between allergy and pollution (10,11);  A proof-of-concept on the digital transformation of health and care to sustain Planetary Health (12);  Clinical trials (13,14).…”
Section: Introductionmentioning
confidence: 99%